Exploring Preservice Science Teachers’ Conceptual Understanding of Wave–Particle Duality through Prompt-Based Learning - Jadnika Amrullah; Nur Ahmad; Sri Rejeki Dwi Astuti; Firdha Yusmar; Ika Dewi Sumiati; Soraya Firdausi; Bartolomeus Kristi Brahmantia Putra; Israel Ametepey (Jurnal Inovasi Pendidikan IPA, 2026)
This study aims to explore preservice science teachers’ conceptual understanding of wave–particle duality and to examine the role of prompt-based learning in supporting conceptual change. A qualitative-dominant mixed-methods design was employed involving 32 preservice science teachers enrolled in a physics education course. Data were collected through pre- and post-instruction open-ended conceptual tasks and written responses to structured prompts during instruction. Quantitative analysis was used to identify trends in conceptual understanding, while qualitative thematic analysis examined the nature and development of participants’ explanations. The results indicate that prior to instruction, most participants demonstrated classical or hybrid reasoning regarding wave–particle duality. After engaging in prompt-based learning, there was a significant increase in quantum-consistent conceptual understanding, accompanied by a shift from ontological to epistemic, model-based reasoning. The findings also reveal that explanation, reflective, and prediction–evaluation prompts played a key role in fostering conceptual coherence and metacognitive awareness, although some hybrid reasoning persisted. These results highlight the potential of prompt-based learning as an effective instructional approach for supporting preservice science teachers’ understanding of abstract quantum concepts.